2008
DOI: 10.1111/j.1537-2995.2008.01800.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of D sensitization after mismatched transfusion of blood components: toward optimal use of RhIG

Abstract: Transfusion of D+ red blood cells (RBCs) into D- recipients, whether through whole blood, RBC, or platelet (PLT) transfusion, can lead to alloimmunization with associated risks of hemolytic reactions from subsequent mismatched transfusion. The incidence of D alloimmunization in various transfused patient populations may be different from that reported in normal subjects or in pregnancy, but prevention of D alloimmunization after mismatched transfusion can be achieved using RhIG. An optimal approach to the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 69 publications
0
31
0
Order By: Relevance
“…It is clear that the RhD antigen is the most potent immunogen of all of the red cell antigens; 85% of RhD-negative individuals will sensitize (form anti-D) after challenge with a 200 mL transfusion of red cells, although more recent data suggests this is far lower. 12 Although as little as 0.1 to 1 mL of RhD-positive red cells can stimulate antibody production, the volumes of FMH are generally small, which contributes to relatively low alloimmunization rates in pregnancy. Before Rh(D) immunoprophylaxis was implemented in 1968, 16% of ABO compatible D-negative mothers with D-positive infants developed anti-D antibody.…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%
“…It is clear that the RhD antigen is the most potent immunogen of all of the red cell antigens; 85% of RhD-negative individuals will sensitize (form anti-D) after challenge with a 200 mL transfusion of red cells, although more recent data suggests this is far lower. 12 Although as little as 0.1 to 1 mL of RhD-positive red cells can stimulate antibody production, the volumes of FMH are generally small, which contributes to relatively low alloimmunization rates in pregnancy. Before Rh(D) immunoprophylaxis was implemented in 1968, 16% of ABO compatible D-negative mothers with D-positive infants developed anti-D antibody.…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%
“…The administration of appropriate doses of Rh immunoglobulin (20 mg of Rh immunoglobulin per 1 mL of RBCs given within 72 h of exposure is suggested) can prevent immunization of Rhnegative patients exposed to Rh-positive products. 132 One group described favorable results of transfusing only ABO-identical red cells and platelet products for patients undergoing autologous or allogeneic transplantation, claiming improved survivals compared with results published by other transplant programs. 133 A retrospective study of pediatric patients found a correlation between ABO-incompatible plasma infusions and hepatic sinusoidal syndrome, possibly a consequence of expression of ABO antigens in the liver.…”
Section: Transfusion Support For Red Cell-incompatible Transplantationmentioning
confidence: 99%
“…To our knowledge, there have been no randomized clinical trials evaluating the appropriate dosing regimen for IV RHIG administration. Rather, the current standard-of-care has emerged from sporadic case reports and a small number of studies of human volunteers available in the literature over the previous 40 years [9].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, an IV RHIG dose of 20 lg per milliliter of D1 RBCs (or per 2 mL of whole blood) has been successful in preventing alloimmunization to mismatched RBCs when given within 72 h [9]. As each unit of blood was estimated to contain 200 mL and based on a requirement of 20 lg IV RHIG per milliliter of D1 RBCs, 27 vials, each containing 300 lg of IV RHIG, were estimated to be necessary for prophylaxis.…”
Section: Case Reportsmentioning
confidence: 99%